2022
DOI: 10.3390/medicina58091251
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Significances of Positive Surgical Resection Margin after Radical Prostatectomy for Prostatic Cancers: A Meta-Analysis

Abstract: Background and Objectives: This study aims to elucidate the positive rate and the clinicopathological significance of surgical margin after radical prostatectomy (RP) through a meta-analysis. Materials and Methods: This meta-analysis finally used 59 studies, including the information about the positive surgical margin (PSM) and those clinicopathological significances after RP. The subgroup analysis for the estimated rates of PSM was evaluated based on types of surgery, grade groups, and pathological tumor (pT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…Furthermore, an additional limitation of this study is the absence of comparative analysis with other established techniques of RARP Finally, due to the concerns of surgical margins and urinary leakage, we only restricted our inclusion criteria to low-median risk PCa patients with comparatively small prostate volumes. It had been reported that the positive surgical margin rates after radical prostatectomy ranged from 6.2% to 71.5%, and patients with positive surgical margins had worse BCR-free survivals than those without positive surgical margins ( 19 ). Kim et al found that tumor location was not a risk factor of postoperative biochemical recurrence ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, an additional limitation of this study is the absence of comparative analysis with other established techniques of RARP Finally, due to the concerns of surgical margins and urinary leakage, we only restricted our inclusion criteria to low-median risk PCa patients with comparatively small prostate volumes. It had been reported that the positive surgical margin rates after radical prostatectomy ranged from 6.2% to 71.5%, and patients with positive surgical margins had worse BCR-free survivals than those without positive surgical margins ( 19 ). Kim et al found that tumor location was not a risk factor of postoperative biochemical recurrence ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…It had been reported that the positive surgical margin rates after radical prostatectomy ranged from 6.2% to 71.5%, and patients with positive surgical margins had worse BCR-free survivals than those without positive surgical margins ( 19 ). Kim et al found that tumor location was not a risk factor of postoperative biochemical recurrence ( 19 ). However, it was notable that there was no significant correlation between positive surgical margin and cancer-specific survivals according to the long-term follow-up data ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSM is a complex issue for urologists since it is strongly associated with worse clinical outcomes ( 6 , 39 ). The cutoff PSM rate in our study was 27.5%, which is high in view of the global PSM rate of 6.5-32% ( 6 ), but in the Asian region, the cutoff rate has been approximately 21.9%-38.3%, making our rate low to moderate there ( 19 , 40 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Radical prostatectomy (RP) is a therapeutic procedure for clinically localized and locally advanced PCa that aims to surgically eradicate malignant tumors and ensure complete removal of the entire prostate gland and surrounding structures for optimal oncological control. However, positive surgical margins (PSMs) still occur after RP and may increase the risk of postoperative biochemical recurrence [ 15 , 16 , 17 ]. Since PSMs may suggest an adverse prognosis for PCa treatment, there is a need to identify risk factors for PSMs.…”
Section: Introductionmentioning
confidence: 99%